A. AVLONI - ENLIGHTENER, TEACHER AND SCHOOL REFORMER (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the role of A. Avloni, a famous Uzbek writer, playwright, educator and teacher, who made a significant contribution to the development of pedagogical thought on the ideas of the socio-political movement Jadidism.